2009
DOI: 10.1089/jir.2008.0079
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-α Conditioned Sensitivity to an Anti–Epidermal Growth Factor Receptor Monoclonal Antibody in a Human Lung Cancer Cell Line With Intermediate Expression of the Receptor

Abstract: Targeted therapy to the epidermal growth factor receptor (EGFR) seems to be related to its expression level on tumor cells. Interferon-alpha (IFN-alpha) induces growth inhibition but also may up-regulate the EGFR expression in some cancer cell lines. We aimed to determine whether the IFN-alpha combined with an EGFR-specific monoclonal antibody (nimotuzumab) may affect the growth of human tumor epithelial cell lines with different EGFR expression levels. H125, a lung adenosquamous carcinoma, and A431, a vulvar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Previously, many studies reported that IFN-α could activate EGFR signalling by upregulating EGFR expression [ 7 , 8 ]. We investigated whether IFN-α could induce EGFR signalling activation in NSCLC cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, many studies reported that IFN-α could activate EGFR signalling by upregulating EGFR expression [ 7 , 8 ]. We investigated whether IFN-α could induce EGFR signalling activation in NSCLC cells.…”
Section: Resultsmentioning
confidence: 99%
“…There are numerous reports on preclinical studies of interferon (IFN) and its positive synergistic effect when combined with anti-EGFR agents in various tumours, such as renal cell carcinoma [ 2 ], hepatocellular carcinoma [ 3 ], and bladder carcinoma [ 4 ]. In addition, many studies have verified the positive combined effect of IFN and EGFR-TKI in human colon cancer cells [ 5 , 6 ] and head and neck cancer cells [ 7 ]; it is hypothesised that IFN can activate EGFR signalling by upregulating EGFR [ 8 ]. As EGFR-TKI has been applied primarily in advanced NSCLC, our experiment was designed to explore the combinational or sequential role of IFN-α and gefitinib in NSCLC cells possessing different genotypes, and to determine whether the synergistic effect of this combination therapy can occur in NSCLC.…”
mentioning
confidence: 99%
“…In contrast, H460, H1299 and H1975 cells show a low level of surface EGFR expression (Akashi et al, 2008). H125, a lung adenosquamous carcinoma cell line expresses intermediate level of EGFR (Diaz et al, 2009). Even in similar lung adenocarcinoma cell lines with increased expression of EGFR, some overexpress wild-type EGFR, while others overexpress mutant-type EGFR.…”
Section: Discussionmentioning
confidence: 98%
“…IFNα pre-treatment followed by a combination of IFNα plus Erlotinib significantly enhanced the sensitivity of colon cancer cell lines 31 . IFNα enhanced the sensitivity to an anti-epidermal growth factor receptor monoclonal antibody (Nimotuzumab) in a human lung cancer cell line with intermediate expression of the receptor 32 . Low dose of IFNα intensified antineoplastic effect of a histone deacetylase -inhibitor, valproic acid, and the mammalian target of rapamycin inhibitor everolimus in prostate cancer cells 33 .…”
Section: Discussionmentioning
confidence: 99%